2016
DOI: 10.1002/ejoc.201600092
|View full text |Cite
|
Sign up to set email alerts
|

One Step Synthesis of Calix[n]quin­ones through the HClO4/PbO2‐Mediated Oxidation of Calix[n]arenes

Abstract: A procedure using HClO 4 and PbO 2 allows the straightforward oxidation of para-substituted and unsubstituted calix[n]arenes into the corresponding calix[n]quinones in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…TLC‐MS analysis of the solution of S3 plus excess Cu(ClO 4 ) 2 after an NH 4 Cl wash and filtration through a silica pad shows m/z 1177 consistent with the sodium ion of the calixdiquinone, S3‐Q 2 . Oxidative routes to calixdiquinones generally involve thallium or lead reagents and whilst Chung's Fe 3+ sensing by a 1,2,4‐oxadiazole‐substituted calixarene provides precedence for redox mediated, transition metal ion sensing promoting calix[4]diquinone generation, as far as we can tell this work represents the first isolation of a Cu(II) generated calix[4]diquinone.…”
Section: Resultsmentioning
confidence: 99%
“…TLC‐MS analysis of the solution of S3 plus excess Cu(ClO 4 ) 2 after an NH 4 Cl wash and filtration through a silica pad shows m/z 1177 consistent with the sodium ion of the calixdiquinone, S3‐Q 2 . Oxidative routes to calixdiquinones generally involve thallium or lead reagents and whilst Chung's Fe 3+ sensing by a 1,2,4‐oxadiazole‐substituted calixarene provides precedence for redox mediated, transition metal ion sensing promoting calix[4]diquinone generation, as far as we can tell this work represents the first isolation of a Cu(II) generated calix[4]diquinone.…”
Section: Resultsmentioning
confidence: 99%
“…In 2015, Lavendomme [22] suggested that PbO 2 and 70% HClO 4 could directly oxidize 3a and 1a-c to the corresponding 2a-c under milder conditions. Scheme 3Employing PbO 2 and 70% HClO 4 as the oxidant, CH 2 Cl 2 / acetone (v/v = 1 : 1) as the solvent, 1a was oxidized to 2a at room temperature, and the yield could reach 42%.…”
Section: One-step Oxidationmentioning
confidence: 99%
“…quinones (n = 4, 6, 8). [22] It mainly includes three steps: diazo coupling, reduction, and oxidation. The calculation results of some yields have been revised and highlighted in Scheme 4.…”
Section: Scheme 3 Pbo 2 /Hclo 4 -Mediated Oxidation Of Calix[n]arenementioning
confidence: 99%
“…An alternative method reported for the synthesis of calix [4]quinones from p-t-butylcalixarenes is oxidation with PbO2/HClO4, which has been reported to give similar yields to the thallium trifluoroacetate oxidation method. 14 Calix[4]quinone synthesis has also been reported through electrochemical oxidation. 1 This method does not require chemical oxidising reagents, but can be more difficult to scale up.…”
Section: Introductionmentioning
confidence: 99%